2001
DOI: 10.1210/jcem.86.12.8111
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Enhances Appetite and Increases Food Intake in Humans

Abstract: Ghrelin is a recently identified endogenous ligand for the growth hormone secretagogue receptor. It is synthesized predominantly in the stomach and found in the circulation of healthy humans. Ghrelin has been shown to promote increased food intake, weight gain and adiposity in rodents. The effect of ghrelin on appetite and food intake in man has not been determined. We investigated the effects of intravenous ghrelin (5.0 pmol/kg/min) or saline infusion on appetite and food intake in a randomised double-blind c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
748
9
33

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,804 publications
(828 citation statements)
references
References 20 publications
21
748
9
33
Order By: Relevance
“…The present findings support a physiological role for circulating ghrelin in food intake, appetite as well as meal initiation (Egecioglu et al, 2011; Wren et al, 2000, 2001a,b), as we here showed that NOX‐B11‐2 reduced food intake in alcohol‐drinking rats. Supportively, previous studies show that NOX‐B11‐2 decreased food intake in rodents via ghrelin‐dependent mechanisms (Kobelt et al., 2006; Shearman et al., 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings support a physiological role for circulating ghrelin in food intake, appetite as well as meal initiation (Egecioglu et al, 2011; Wren et al, 2000, 2001a,b), as we here showed that NOX‐B11‐2 reduced food intake in alcohol‐drinking rats. Supportively, previous studies show that NOX‐B11‐2 decreased food intake in rodents via ghrelin‐dependent mechanisms (Kobelt et al., 2006; Shearman et al., 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Human studies show that ghrelin increases the sensation of hunger and appetite. (Wren et al., 2001a). The plasma levels of ghrelin rise preprandially and fall postprandially in humans as well as in rodents, implying that ghrelin induces meal initiation (for review, see Egecioglu et al., 2011).…”
mentioning
confidence: 99%
“…Its actions include a role in appetite regulation and obesity (Wren et al 2001), while the evidence regarding its influence on adipogenesis is contradictory (Zhang et al 2004a). Energy homeostasis is directly associated with reproductive function and the importance of ghrelin in a range of reproductive processes, including steroid hormone regulation and embryo development, has recently been demonstrated (Barreiro & Tena-Sempere 2004).…”
Section: Introductionmentioning
confidence: 99%
“…34 , 35 For example, a vaccine formulation has been created in which PspA is fused as a carrier protein to recombinant ghrelin, a peptide hormone produced in the stomach (ghrelin–PspA). Because ghrelin increases appetite (and thus increases food intake) and decreases energy expenditure, 36 antibody against ghrelin theoretically could restore the balance between food intake and energy expenditure, leading to homeostasis and preventing obesity. Indeed, nasal administration of ghrelin–PspA with cyclic diguanosine monophosphate as an adjuvant increased antigen-specific serum IgG levels and decreased body weight in mice with diet-induced obesity.…”
Section: Application Of Cchp For Nasal Vaccines Against Non-infectioumentioning
confidence: 99%